PMO-101 Enteral nutrition in acute pancreatitis: nasogastric or nasojejunal?. (28th May 2012) - Malde, D J; Suppiah, A; Arab, T; Menon, K; Smith, A M
Abstract : Introduction: Enteral feeding is beneficial in patients with severe acute pancreatitis. A published series suggests 100% can be fed via the nasogastic (NG) route. Methods: 146 consecutive patients (January–December 2010) admitted with acute pancreatitis (AP) were reviewed to assess the safety and tolerance of NG feed. In all severe AP patients nutrition was initially delivered via an NG tube, if they were not absorbing a nasojejunal (NJ) tube was inserted. Results: 29 patients were identified as having poor outcome. 127 (87%) patients were able to commence oral intake within 72 h of admission. 19 (13%) patients required additional enteral or parenteral nutritional support. 16 patients were commenced on NG feed but two patients needed conversion to NJ feed. Three patients were directly commenced on NJ feed but one needed conversion to parenteral feed. Only one patient had been commenced on parenteral feed prior to transfer. Need for nutritional support was a significant indicator of poor outcome; morbidity 13/19 vs 12/127 (p<0.0001) and mortality 6/19 vs 1/127 (p<0.0001). Conclusion: Nasogastric feeding is well tolerated in the majority (73.7%) of patients with severe AP. NG feeding should be first line, but if failing a rapid change to the NJ route instituted. Competing interests: None declared.